Underwater antenna design characterization for tropical shallow water oilfield applications: article / Mohd Hafiz Badiozaman - Badiozaman, Mohd Hafiz (2017)
This project presents the design characterization of underwater antenna for oilfield applications. The design specification is focused on Tropical Shallow Water environment to suit with Malaysia’s Oil and Gas industry where majority of the oilfields are located within this region (depth between water surface and seabed is less than 500 feet).